(untitled) (Scripta : English Department Journal, 2025)
This study explores the perceptions of eleventh-grade students at SMK N 1 Purworejo, SMK PN 2 Purworejo, and SMK TKM Teknik Purworejo regarding the influence of motivation and self-confidence on their English-speaking skills. Employing a qualitative case study approach, the research involved 30 student participants through semi-structured interviews and questionnaires. The findings reveal that students with high levels of motivation and self-confidence generally demonstrate stronger English-speaking abilities. However, a number of these students continued to experience anxiety and apprehension during speaking tasks. Conversely, students with low motivation and self-confidence face significant challenges, such as self-doubt, public-speaking anxiety, limited vocabulary, and fear of mispronunciation. Despite these barriers, many of them express a strong desire to improve through consistent practice. These results highlight the importance of fostering both motivation and self-confidence to support students in developing their English-speaking skills.